Vliv automatizace obráběcích procesů na průchod zakázky firmou - Pavelka, David (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2022)
Cílem této diplomové práce zhodnocení vlivů automatizace na obráběcí procesy, jež mají silný význam v souvislosti s průchodem zakázky firmou. Závěrečná práce je zpracována ve spolupráci s firmou FERMAT CZ, s.r.o, sídlící v Brně. Teoretická část je věnována detailní rešerši současného stavu vědy a techniky a systémovému rozboru řešené problematiky. Praktická část je zaměřená na projekční návrh a zhodnocení změn ve výrobě zmíněné firmy. Veškeré detaily jsou podloženy výpočty, tabulkami a grafickými ilustracemi v textu závěrečné práce.

The goal of this master's thesis is valorisation of automation influences, affecting machine processes, which has strong importance on the passage of the order through the company. Master's thesis is processed in cooperation with FERMAT CZ, s.r.o company, which is based in Based. Theoretical part is focused on detailed research of current state of science and technology and system analysis of solved problems. Practical part is focused on design proposal and evaluation of changes in the production of the mentioned company. All the details are based on calculations, tables and graphic illustrations in the text of the final thesis.
The influence of automation of machining processes on the passage of the order through the company
Keywords: Automatizace; strojní zařízení; obráběcí proces; firma; výrobní podnik; zero point systém; zlepšení; inovace; srovnání; Automation; machinery; machining processes; company; manufacturing company; zero point system; improvement; innovation; evaluation